Differentiation Strategy in the Brazilian Coffee Market - Saes, Maria Sylvia Macchione; Escudeiro, Fulvia Hesse; Silva, Christian Luiz da (Review of Business Management, 2007)
This article aims to verify whether Brazilian consumers have perceived the differentiation strategies of roasting and grinding companies. For that purpose, the profile of the demand for different types of coffee was correlated with their consumption history (price and quantity). 2002 and 2004 monthly data series from Sao Paulo metropolitan region were classified into the following groups of coffee products: Gourmet, Ground Traditional and Vacuum Ground. The main results showed a behavioral change, albeit small, in the period studied. Compared against the Traditional type, the Gourmet and Vacuum types have gained market share, once they present a higher added value. Considering that there was an almost imperceptible change in the budgetary restriction of the consumers in the period and region analyzed, it is concluded that the strategic change, i.e., added value through differentiation in the characteristics of the product, mainly the sensorial one, allowed for an increased participation of coffee in the basket of consumers goods. Key-words: Coffee. Differentiation. Demand. Strategy.